Identifying the Implementation of Three Attributes of Green City in Gorontalo City - Mantali, Zamaludin (Sriwijaya Journal of Environment, 2023)
Over time, population growth in Gorontalo City will continue to increase. While the condition of land for housing will not increase. This is certainly one of the problems that requires seriousness in handling it. Based on data from the Central Bureau of Statistics of Gorontalo Province in 2012 to 2021, population growth in Gorontalo City continues to increase from 189,476 people to 199,788 people. This causes a decrease in the quality of the environment in Gorontalo City which results in the emergence of slum areas and climate change, in this case global warming. As an effort to overcome these problems, Gorontalo City is currently implementing the Green City concept. Green City is an environmentally friendly and sustainable city development concept. In this research, the author uses Qualitative Research Method by identifying the distribution of three Green City attributes to find out how important the improvement of the three attributes is in the Green City concept in Gorontalo City. The three attributes that the author refers to include Green Open Space, Green waste, and Green Community. The output of this research is an increase in the principles of Green City attributes from each element of the Green City attributes so as to create a Sustainable and Environmentally Friendly Gorontalo City Regional Development supported by the city community itself.Keywords: Green City, Environment, City of Gorontalo.